(untitled) (Research, Society and Development, 2022)
In 2020, the Brazilian Government declared that the pandemic was a case of a health and health crisis, in response to the measures taken to combat the virus, such as: the closing of trade and the curfew, brought a distance between the customer and the market. In view of these events, many enterprises had to adapt to the emergence of the online market and information systems. In this way, the present literature review seeks to understand what were the problems faced by micro-entrepreneurs in the use of information technology during the COVID-19 pandemic period, as well as to better explore what were the difficulties of the enterprises in remaining in the market with the difficulties cited by reading selected articles in the Google Scholar database from 2020 to 2022. The general objective of this review is to present, through scientific publications, studies already prepared on the actions that microentrepreneurs performed during the pandemic period and How technology has influenced this process. As a result of the discussion, it was observed that the main difficulty was the adoption of new strategies to adapt to online commerce.